2003
DOI: 10.1080/0144361021000043128
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre evaluation of the two-layered repair of postpartum perineal trauma

Abstract: We set out to compare a policy of two-layered postpartum perineal repair leaving the skin unsutured with a policy of three-layered repair, which involved skin closure. Parturients who sustained a second-degree tear or an episiotomy in four Nigerian centers were randomised to have either a two-layered repair (417 women) or a three-layered repair (406 women). Fewer women in the two-layered group reported perineal pain at 48 hours (57% vs. 65%, relative risk [RR] 0.87, 95% confidence interval [CI] 0.78-0.97) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…Again, suturing such slightly damaged perineum can be discussed in the interest of optimizing the perineal comfort of patients. Several studies show that not suturing the skin reduces perineal pain and dyspareunia, without increasing the risk of the wound’s reopening [23]. No third- or fourth-degree perineal tears were observed during this study, which is in line with the very low rate in our department – respectively, 4% and 2% based on our 2010 study [24].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Again, suturing such slightly damaged perineum can be discussed in the interest of optimizing the perineal comfort of patients. Several studies show that not suturing the skin reduces perineal pain and dyspareunia, without increasing the risk of the wound’s reopening [23]. No third- or fourth-degree perineal tears were observed during this study, which is in line with the very low rate in our department – respectively, 4% and 2% based on our 2010 study [24].…”
Section: Discussionsupporting
confidence: 82%
“…Prospective studies have shown that second degree occur in 13-36% of women who deliver vaginally [5, 1722] . Based on our usual rates of perineal trauma in nulliparous women, we hypothesized that the frequency of second-degree tears would be 28% in the non-exposed group and 10% in the exposed group [23]. No studies in the literature are available on the rate of perineal tears after CM.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported favorable outcomes with the use of skin adhesive, but they looked mainly at cosmetic results and only included dry skin lesions under low tension (9, 11, 16). The use of skin adhesive in wounds under higher tension is reported to have worse results than conventional sutures (7).…”
Section: Discussionmentioning
confidence: 99%
“…The average number of enrolled participants per midwife was five throughout the study period (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. No difference was seen with respect to time for completion of repair or usage of suture material.…”
Section: Resultsmentioning
confidence: 99%
“…Several, large randomised trials have shown that the continuous suturing technique with subcutaneous stitches placed well ª 2008 The Authors Journal compilation ª RCOG 2008 BJOG An International Journal of Obstetrics and Gynaecology below the perineal skin surface is superior to interrupted stitches in all layers, including stitches through the perineal skin. [3][4][5] Pain and discomfort can also be reduced using a rapidly absorbed synthetic suture material instead of products with longer absorption time. 4,6,7 There is scanty evidence on effective pain-relieving methods during perineal repair.…”
Section: Introductionmentioning
confidence: 99%